A 125-year journey and quest for better choice: OA or LA? - Ranjan, Rajiv; Jha, Ajay Kumar; Sinha, Kishore K. (International Surgery Journal, 2018)
Appendectomy is now 125years old and we salute it. It is the operation for the removal of an inflamed symptomatic appendix to cure acute appendicitis (AA), the commonest surgical emergency world over. There are two variants of appendectomy: 1. Open and 2. Laparoscopic. Open appendectomy (OA) dominated the surgical word for about 85years and in 1980 was challenged by the laparoscopic appendectomy (LA). Thirty years since then a pseudo controversy continues as to which is a better choice despite a lot of literature to support LA. Using the terms laparoscopic appendectomy, open appendectomy and appendicitis, a literature search was made using Medline and google. About 2100 citations were analyzed and several meta-analyses were studied to resolve the controversy. Laparoscopic appendectomy is worth recommending as an effective and safe procedure for acute appendicitis in both adults and children in all types of symptomatic appendicitis. Overall LA is more patient friendly than open appendectomy and deserves to be a gold standard surgical modality.